Solanaceae and Cucurbitaceae Crops - Tzortzakis, Nikos G.; Alkan, Noam; Ziv, Carmit; Korsten, Lise (My University, 2019)
The development of high-value crops for domestic consumption and export is a priority for economic development and improved livelihoods worldwide. Fruit vegetable consumption has increased in the recent decades, with increased demand for tomato, pepper, and eggplant as well as cucumber, melon, watermelon, and squash belonging to Solanaceae and Curcubitaceae families, respectively. The nutritional value of fruit vegetables has promoted this trend. However, losses of horticultural produce are a major problem after harvest, which includes all points in the value chain from production in the field to the food placed on consumers’ plates. Not only are losses clearly a waste of food but also they represent a similar waste of human labor, farm inputs, livelihoods, investment, and scarce resources such as water. Current sanitation means are ineffective and need to be optimized for specific commodities, due to the diversity of produce, opportunistic pathogens, storage conditions, and produce value. New and expanding trends in food and agriculture for chemical-free products have prompted the research to find commercially viable alternatives to conventional, synthetic pesticides, or options that work integrated programs to minimize their use have been proposed.